Implementasi Intelligence Quotient, Emotional Quotient, dan Financial Spiritual Quotient Terhadap Kinerja Pimpinan Satuan Kerja Perangkat Daerah di Kabupaten Parigi Moutong - Bakri Bakri. (Al-Buhuts, 2018)
This study aims to 1.) To determine and analyze simultaneous influence of Intelligence Quotient, Emotional Quotient, and Financial Spiritual Quotient towards the Performance of Regional Working Units Leaders in Parigi Moutong Regency 2). To determine and analyze partial influence of Intelligence Quotient on the Performance of Regional Working Units Leaders in Parigi Moutong Regency 3). To determine and analyze partial influence of Emotional Quotient on the Performance of Regional Working Units Leaders in Parigi Moutong Regency. 4). To determine and analyze partial influence of Financial Spiritual Quotient on the Performance of Regional Working Units Leaders in Parigi Moutong Regency. Results of the study concludes: 1). The variables of Intelligence Quotient, Emotional Quotient, and Financial Spiritual Quotient simultaneously shown a significant influence the performance of Working Units Leaders in Parigi Moutong Regency with R-Square (0.720). 2). Intelligence Quotient variable partially shown a significant influence on the performance of Working Units Leaders in Parigi Moutong Regency. 3). Emotional Quotient variable partially shown a significant influence on the performance of Working Units Leaders in Parigi Moutong Regency. 4). Financial Spiritual Quotient variable partially shown a significant influence on the performance of Working Units Leaders in Parigi Moutong Regency.